The test-retest reliability of three different hip joint centre location techniques - Sinclair, J.; Taylor, P. J.; Currigan, G.; Hobbs, S. J. (Movement & Sport Sciences - Science & Motricité, 2014)
The hip joint centre (HJC) is essential in kinematic analyses. Three principal techniques exist for the estimation of the HJC, anatomical, functional and projection, although their test-retest has not been established. Fifteen participants ran at 4.0 m/s ± 5%; 3-D kinematics of the hip and knee were collected. The HJC was defined twice using each technique (test-and-retest) and the kinematic data was applied to both. The results show significant test-retest differences in the coronal and transverse planes using the functional and projection techniques. Strong test-retest intraclass-correlations were observed for all techniques although the anatomical method was associated with the highest reliability. The anatomical technique for HJC estimation appears to be the most reliable; therefore its utilization for 3-D analyses is recommended.